On Earth as in Heaven : The Lord's Prayer from Jewish Prayer to Christian Ritual - Clark, David (Book collections on Project MUSE., 2017)
Convinced that we no longer have immediate access to the sense of Jesus' words but must account for the history of its "effects," David Clark seeks to trace the meaning of the Lord's Prayer through the early centuries of the faith. Clark begins by arguing that the prayer's origin in Jesus' oral teaching, then traces its transmission and representation in the Gospels of Matthew and Luke and the Didache, then examines the first full commentary on the prayer, that of Tertullian in the third century CE.